Stress in the Roman Catholic priesthood: "Harvest for a millennium" - Doyle, Una (2005)
This thesis investigates the existence of stress in the Roman Catholic priesthood. A transactional model of stress is adopted as a heuristic for this investigation. Here, stress is seen as the relationship between features of the work environment, as appraised by clergy themselves, and various indicators of diminished well-being e.g. poorer self reported health, lower self-esteem and increased pessimism about the role and effectiveness of the priest in the future. This model also places considerable emphasis upon the possible role of perceived support in the overall aetiology - or amelioration - of stress. Using this transactional model as a guide, seventeen work environment stressors, were identified on the basis of qualitative and quantitative investigations with a total sample of 189 priests drawn from four dioceses. The qualitative investigation comprised twelve in-depth interviews with an opportunistic sample of clergy. The focus of these interviews was to determine the antecedents and consequences of stress as perceived by members of the clergy. On the basis of the interview data a bespoke questionnaire was developed for distribution to a broad sample of priests. The questionnaire measured both antecedents (work environment factors) and consequences (impacts on well-being) as well as perceptions of the support available to priests both inside and outside the Church. The data to be presented show that it is the contradictions that many priests have to deal with which are often pivotal in the aetiology of stress e.g. the implementation of Canon Law in an increasingly secular world. The multiplicity and diversity of roles that priests now have to fulfil - whether at Diocesan or parochial level, is also a key factor, as are the daily parish/diocesan administration duties that priests have to undertake and the increasingly 'convenience stores mentality' (as clergy see it) of the Church community. Very little support in dealing with these issues was perceived to be available to them by many priests within the sample. The implications of these results are discussed both in terms of their correspondence with findings in general occupational stress research and in terms of a proposed rudimentary stress management programme that might be implemented to help manage stress within the Roman Catholic priesthood.